Optimizing medication therapy in older hospitalized patients. Identifying potentially inappropriate medications and testing an interdisciplinary intervention - Johansen, Jeanette Schultz (UiT The Arctic University of Norway, 2022)
The overall aim of this thesis is to provide knowledge on potentially inappropriate medications (PIMs) in hospitalized older patients and to investigate how clinical pharmacist services in an interdisciplinary setting can contribute to medication optimization and improve patient outcomes. First, we used national health registers to investigate how admissions to Norwegian geriatric hospital wards affected PIM use. More than half of the 715 patients included in the study used PIMs after discharge. Hospitalization did not reduce the use of PIMs but may have increased use depending on how we measured PIMs. Second, we designed a 5-step intervention, introducing a clinical pharmacist in the ward teams working by the integrated medicines management (IMM) model to optimize medication use and improve communication with primary care. The intervention was tested in older patients ≥70 years admitted to two internal medicines wards at the University Hospital of North Norway. We applied a non-blinded randomized controlled trial, where 516 acutely admitted patients were randomized into an intervention group and a standard care group (1:1). The primary outcome was the rate of emergency medical visits (readmissions and emergency department visits) 12 months after discharge. Many medication discrepancies and MRPs were identified and solved in intervention patients, suggesting that the intervention optimized medication use. However, no significant reduction in the rate of emergency medical visits was observed in intervention patients versus control patients, nor did we observe any significant effects on time to the first emergency medical visit, 30-days readmissions rate, length of index hospital stay or mortality. Overall, this thesis demonstrates a need to optimize medication therapy in older hospitalized patients. Including clinical pharmacists' services in hospital wards teams may contribute to optimizing medication use, but there is a need for further studies to identify interventions that simultaneously produce meaningful ...